(untitled) (CAHIERS MAGELLANES-NS, 2024)
The conflict following the Military coup in Feb 2021, has plummeted Myanmar into a severe humanitarian crisis including the state of Chin on the western border of Myanmar, bordering Mizoram, India and have led to civilian being injured in bombings, due to landmines, caught in shootings and their villages being burnt in retaliation by the Myanmar military. The humanitarian crisis has forced tens of thousands of people to flee from their homes. Many are internally displaced, and many have sought refuge in Champhai district in Mizoram State in India and this number has been steadily increasing over the past. Both the YMA and the state government have been working to provide humanitarian aid since 2021. More recently The military junta continues to intensify aerial bombardments in Chin State. The Diplomat reports that the population of Chin State has endured 47 airstrikes in the month of April 2023. The UN and other international aid agencies still haven’t been able to provide humanitarian aid in Chin state from within Myanmar due to communication breakdowns and difficulty accessing the affected areas, mainly because the military has cut off all aid especially humanitarian medical aid (The MY Military’s Four Cuts Strategy). UNHCR Myanmar Emergency Overview Map on 17 October 2022 reported 48600 as displaced from Chin into neighboring countries and this number increased to 53,500 in the updated overview published on 01 May 2023. Over 20,000 of these are in Champhai alone.